2015
DOI: 10.1038/srep11205
|View full text |Cite
|
Sign up to set email alerts
|

HIV burden in men who have sex with men: a prospective cohort study 2007–2012

Abstract: We conducted a prospective cohort study among HIV-negative MSM aged 18 years or older between 2007 and 2012 in Beijing, China to measure the rates of incident HIV and identify risk factors for infection. Among 5,800 participants evaluated at enrollment, we identified 486 prevalent cases of HIV (8.4%). Among the 3,625 enrollees who were HIV-negative at enrollment and completed at least one follow-up interview, we identified 440 incident cases of HIV in the follow up period: this constituted an HIV incidence rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…Despite the national efforts in scaling up prevention interventions, men who have sex with men (MSM) in China continue to represent the most affected population by HIV [1, 2]. While HIV epidemics have stabilized or declined among other high-risk populations (e.g., female sex workers, people who inject drugs), HIV prevalence among Chinese MSM had increased from 0.9% in 2003 to 7.7% in 2014 [3].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the national efforts in scaling up prevention interventions, men who have sex with men (MSM) in China continue to represent the most affected population by HIV [1, 2]. While HIV epidemics have stabilized or declined among other high-risk populations (e.g., female sex workers, people who inject drugs), HIV prevalence among Chinese MSM had increased from 0.9% in 2003 to 7.7% in 2014 [3].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the literature often focus on risk factors reported by individuals at or after their HIV diagnosis. [ 4 11 ] A large cohort study in Italy demonstrated a link between previous syphilis diagnosis and HIV infection among MSM. [ 10 ] In Australia, a community-based cohort study in Sydney has showed rectal gonorrhea and anal warts were independent risk factors for HIV acquisition; however, this study did not examine demographic and behavioural characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Men who have sex with men (MSM) in China are highly affected by HIV, with the prevalence increased from 0.9% in 2003 to 7.7% in 2014 (Jia et al, 2015). Chinese MSM are underrepresented in HIV testing and treatment services, contributing to suboptimal coverage in the continuum of care (Y.…”
Section: Introductionmentioning
confidence: 99%